Impact of organizational structure and social support on pro-social rule breaking: A frontline perspective - Lisbeth Mary John; Muhammad Shafi (Cogent Business & Management, 2020)
Scholars over the past two decades have shed significant light on employee pro-social rule-breaking behaviors. Yet, the organizational and contextual variables and their influence on these behaviors are not properly considered. This paper focuses on frontline pro-social rule breaking and examines the influence of two elements of organizational environment; namely, organizational structure and social support, on the three types of pro-social rule breaking, using cross sectional survey data of frontline employees of two Indian-scheduled commercial banks. The results show that organizational structure and social support have differential influences on job-oriented, customer-oriented, and co-worker-oriented pro-social rule breaking. Researchers deliberated the impact of structural elements; namely, participation in decision-making, hierarchy of authority, job codification, rule enforcement, and perception of social support, thus identifying the drivers and inhibitors of the behaviors. Paper also offers guidelines for managing the three types of pro-social rule breaking via managerial practices and policy interventions.
Keywords: D23; 650; co-worker-oriented pro-social rule breaking; customer-oriented pro-social rule breaking; frontline employee; job-oriented pro-social rule breaking; organizational structure; social support